2018
DOI: 10.1063/1.5022131
|View full text |Cite
|
Sign up to set email alerts
|

The software-defined fast post-processing for GEM soft x-ray diagnostics in the Tungsten Environment in Steady-state Tokamak thermal fusion reactor

Abstract: This article presents a novel software-defined server-based solutions that were introduced in the fast, real-time computation systems for soft X-ray diagnostics for the WEST (Tungsten Environment in Steady-state Tokamak) reactor in Cadarache, France. The objective of the research was to provide a fast processing of data at high throughput and with low latencies for investigating the interplay between the particle transport and magnetohydrodynamic activity. The long-term objective is to implement in the future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…These positive results render the implementation of the proposed architecture possible. The suggestions to further investigate GPUs in the previous studies were correct.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…These positive results render the implementation of the proposed architecture possible. The suggestions to further investigate GPUs in the previous studies were correct.…”
Section: Discussionmentioning
confidence: 93%
“…The front‐end impact on the back‐end analysis has been discussed by Krawczyk et al The development of the heterogeneous architecture of FPGAs and HPC servers has been documented by Krawczyk et al with the most relevant advantages of such an approach. The real‐time modes of operation have been presented by Krawczyk et al…”
Section: The Fast Plasma Impurities Diagnostic System For Soft X‐raysmentioning
confidence: 99%
See 2 more Smart Citations
“…Further limitations are introduced by the ES part. Latest analyzes [37,38] have shown that a system based on Xeon e5 S2600 v4 CPU with 10 cores is able to process up to 6.9 million photons per second. However, the system is still under development, and further improvement both regarding the PCIe bandwidth and processing throughput is expected.…”
Section: Current Results For the West Systemmentioning
confidence: 99%